Role Of Mediating Consumption Behavior in The Influence of Saving Behavior on Financial Management Ability Among Generation Z Student in Malang City - Adhitya Maulana Sahputra; Thomas Sosecco; Vika Annisa Qurrata (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the mediating role of consumption behavior in the relationship between saving behavior and financial management ability among Generation Z students in Malang City. The research is grounded in the Theory of Planned Behavior, which emphasizes the role of intention and self-control in shaping financial decision-making. A quantitative approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4 software. The sample consisted of 200 university students aged 18–25 years who have experience using financial technology (fintech) platforms and personal saving activities. The measurement model results show that all constructs meet reliability and validity criteria, with outer loadings above 0.70 and AVE values exceeding 0.50. The structural model findings indicate that saving behavior has a positive and significant effect on consumption behavior (T = 3.303; p = 0.001), and consumption behavior has a significant effect on financial management ability (T = 2.918; p = 0.004). Furthermore, consumption behavior mediates the relationship between saving behavior and financial management ability (T = 3.244; p = 0.001), confirming its crucial role in strengthening the effect of saving discipline on financial outcomes. The R² values of 0.146 for financial management ability and 0.191 for consumption behavior suggest a moderate explanatory level that remains acceptable in behavioral and social science studies. The findings conclude that consistent saving and rational consumption behavior enhance financial management ability among students. Therefore, universities and policymakers should promote behavioral-based financial education programs that integrate saving discipline and consumption awareness to improve students’ financial resilience in the digital financial era.